Position control of an industrial robot using an optical measurement system for machining purposes - Schneider, Ulrich; Drust, Manuel; Diaz Posada, Julian; Verl, Alexander (Cranfield University Press, 2013)
A series of mechanical properties and disturbances limit the accuracy achievable in robotic applications. External control of the end effector position is commonly known as being an appropriate mean to increase accuracy. This paper presents an approach for position control of industrial robots using the pass-through between an industrial CNC and servomotors. A CNC-controlled robot is used together with an external optical measurement system to close the feedback loop of robot end effector and robot controller in order to improve robot accuracy. For short cycle times and implementation reasons a PLC is used for signal processing and control implementation. The relevance of the approach is outlined in experiments. The robot behaviour in free space motion and in machining application is analysed with the optical measurement system and a CMM.
Keywords: Robot position control; robot end effector tracking; robot machining